2014
DOI: 10.6018/analesps.30.3.170831
|View full text |Cite
|
Sign up to set email alerts
|

Búsqueda de sensaciones y consumo de alcohol: El papel mediador de la percepción de riesgos y beneficios

Abstract: Resumen: La búsqueda de sensaciones es una de las variables de personalidad más estrechamente ligadas con la adopción de distintas conductas de riesgo, especialmente el consumo de alcohol y otras drogas. Además, la búsqueda de sensaciones influye en la valoración que los individuos realizan sobre los riesgos y sus posibles consecuencias. El objetivo de este estudio es analizar la relación entre la búsqueda de sensaciones y el consumo de alcohol en una muestra de 356 jóvenes con edades comprendidas entre los 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 51 publications
4
9
0
8
Order By: Relevance
“…Structural equation modeling demonstrated the direct effect of sensation seeking on alcohol drinking in this sample of Mexican youth. These results are theoretically (Hittner & Swickert, 2006;Palacios, 2015a;Roberti, 2004;Zuckerman, 1994) and empirically supported (González-Iglesias et al, 2014;Horvath & Zuckerman, 1993;Zuckerman, 2007;Zuckerman & Kuhlman, 2000). Additionally, the effects are similar to what is reported in several studies (Legrand et al, 2007;Palacios & Cañas, 2010;Romero Saletti et al, 2017;Yanovitzky, 2006).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Structural equation modeling demonstrated the direct effect of sensation seeking on alcohol drinking in this sample of Mexican youth. These results are theoretically (Hittner & Swickert, 2006;Palacios, 2015a;Roberti, 2004;Zuckerman, 1994) and empirically supported (González-Iglesias et al, 2014;Horvath & Zuckerman, 1993;Zuckerman, 2007;Zuckerman & Kuhlman, 2000). Additionally, the effects are similar to what is reported in several studies (Legrand et al, 2007;Palacios & Cañas, 2010;Romero Saletti et al, 2017;Yanovitzky, 2006).…”
Section: Discussionsupporting
confidence: 86%
“…A variety of studies (Hittner & Swickert, 2006;Legrand, Kaltenbach, Joly, et al, 2007;Yanovitzky, 2006;Zuckerman, 1994Zuckerman, , 2007 argue that high levels of sensation seeking correlate positively with alcohol consumption and recently (Smorti & Guarnieri, 2013) positive correlations have been found between the intensity scale and alcohol consumption, as well as between the novelty scale and the amount of alcohol consumed. Research in Latin America (González-Iglesias, Gómez-Fraguela, Gras, & Planes, 2014;Palacios & Cañas, 2010;Romero Saletti, Olivo Chang, Pérez-Aranibar, & Otiniano Campos, 2017;Schmidt, Molina, & Raimundi, 2017) has found that sensation seeking scores tend to be greater among those who consume alcohol, which confirms the importance of the search for sensations in explaining alcohol consumption in young people.…”
Section: Introductionmentioning
confidence: 91%
“…Firstly, the results from the correlation analysis show how variables of alcohol consumption are related to positive expectations about the effects of alcohol and sensation-seeking dimensions (Charles et al, 2016;González-Iglesias et al, 2014). This is the case for both a pattern of binge drinking and the intention to continue consuming alcohol in the short-to-medium term.…”
Section: Discussionmentioning
confidence: 94%
“…Adolescence is characterized by the early experience of new sensations (Azpiazu, Esnaola, & Sarasa, 2015). Many studies have made the association between sensation-seeking and drug consumption (González-Iglesias, Gómez-Fraguela, Gras, & Planes, 2014). These relationships can be particularly evident in adolescence, a time when there are developmental changes (Rodríguez-Fernández, Ramos-Díaz, Madariaga, Arrivillaga, & Galende, 2016), more opportunities for consumption (Staff et al, 2010), and when social support is particularly important (Gázquez et al, 2015a;Hernández-Serrano, Espada, & Guillén-Riquelme, 2016;Ramos-Díaz, Rodríguez-Fernández, Fernández-Zabala, Revuelta, & Zuazagoitia, 2016;Molero, Pérez-Fuentes, Gázquez, & Barragán, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Así, la formación de los docentes en cuanto a conductas de uso y abuso de sustancias, podría repercutir en una percepción mayor de los adolescentes respecto a las consecuencias negativas derivadas del consumo. Igualmente, este hecho se vería reflejado, posiblemente, en la reducción del consumo, ya que la percepción de peligrosidad presenta una alta influencia en el inicio y mantenimiento de esta conducta (González-Iglesias et al, 2014;Salamó et al, 2010).…”
Section: Discussionunclassified